Project management as a tool for effective development and enhancing the competitiveness of startups in the modern business environment - Sergiienko, Tetiana; Venger, Olga (Management and Entrepreneurship: Trends of Development, 2025)
The article examines project management as a strategically important tool for the effective development of startups in today’s competitive business environment. The relevance of the topic is driven by the growing role of startups as drivers of the innovation economy and the need to identify effective management approaches to ensure their sustainable operation and competitiveness. In the context of rapid technological changes, market volatility, and high levels of uncertainty, startups are compelled to adopt flexible management models, with the project-based approach taking a leading role.The aim of this study is to justify the use of project management in startup administration, to analyze contemporary project management methodologies in terms of their relevance to the specific needs of startups, and to identify key factors that contribute to increasing the effectiveness and competitiveness of newly established enterprises.To achieve this goal, a set of general scientific and specialized research methods was used: theoretical analysis of academic sources to explore the conceptual foundations of project management; a systems approach to reveal the relationship between project management and the level of startup competitiveness; as well as expert evaluation and synthesis of practical experience to develop applied recommendations for the implementation of the project-based approach.The results of the study demonstrate that successful startup management requires a flexible, adaptive, and innovative approach that enables efficient use of limited resources, risk mitigation, enhanced team performance, and rapid responsiveness to external changes. A model for integrating elements of project management into the strategic and operational activities of startups is proposed. Several key factors influencing the improvement of competitiveness were identified, including clearly defined project goals and objectives, effective team communication, ongoing progress monitoring, speed of decision-making, and capacity for innovation.The practical significance of the findings lies in their applicability by startup founders, innovation project managers, aspiring entrepreneurs, and investors when developing business strategies, managing risks, building effective teams, and increasing the overall resilience of new ventures to external challenges.JEL Classification: L26, M13, M21